Frozen (iced) effect on postmortem CT – Experimental evaluation. Issue 4 (December 2015) - Hyodoh, Hideki; Ogura, Keishi; Sugimoto, Miyu; Suzuki, Yuya; Kanazawa, Ayumi; Murakami, Rina; Shimizu, Junya; Rokukawa, Masumi; Okazaki, Shunichiro; Mizuo, Keisuke; Watanabe, Satoshi
Abstract: The aim of this study is to experimentally evaluate the computed tomography (CT) attenuation of water, saline, iced saline and water ice cubes in order to relate these measurements to low density findings of cadavers on PMCT. Comparing the fluids with the iced materials, the CT number was lower in iced (frozen, with gas) saline (fNaCl) and ice cubes (frozen, without gas) (fH2 O) than in saline (NaCl) and tap water (H2 O). The fNaCl, which contained small air bubbles, presented significant lower CT number than fH2 O. The fNaCl and fH2 O showed around −80 HU and the values were concordant with the theoretical result. In cases where low density is found when a cadaver is undergoing a CT examination at low temperature, including the freezing effect as a new differential diagnosis could result in more accurate PMCT interpretation. Highlights: The "iced or frozen effect" using an experimental model for PMCT is evaluated. Ice showed about −80 Hounsfield Unit (HU) as CT value. The tissue appearance on PMCT is dependent on the physical condition of the corpse. The freezing (iced) effect is a differential diagnosis on PMCT that has to be known.